INDIVIDUAL PSYCHOLOGY - Ravshanqulova Madina Alisher qizi, Yuldoshev Tojiddin Abdukarimovich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
Feelings of inferiority are the main part of individual psychology. Feelings of inferiority are manifested equally in children and adults. If feelings of inferiority develop from childhood, it will have a negative impact on the child's future. Considering that feelings of inferiority threaten the child's personality, scientists began to study the factors that cause it and ways to prevent it. Research has shown that birth order also plays an important role in the development of feelings of inferiority. This article examines the theory of Alfred Adler and several scholars.